Torrential floods in Malaysia: Assessing the loss and vulnerabilities in three Kelantan villages - Karim, A.H.M Zehadul; Md. Noon, Hazizan; Mohamad Diah, Nurazzura; Tajuddin, Nor Azlin; Mustar, Sohela (Mediterranean Center of Social and Educational Research Publishing, 2016)
This research is an attempt to explore the socio-economic loss and vulnerabilities of the people in three villages of Kelantan State who have been considered as the worst victims of the calamity in December 2014 Flood in Malaysia. Three villages Kg.Laloh, Kg Manjor and Kg Manik Urai Lama were chosen purposively which later were surveyed most extensively to make the study totally enumerated in nature. As part of the qualitative study, the research conducted three FGDs and ten in-depth interviews. Findings of the study indicate that with a few exceptions, the great majority of the villagers regardless of their sociodemographic position, suffered badly from the floods in terms of losing their homes, food, pure drinking water and having no transport and carrier for immediate shiftment. In addition to these vulnerabilities, villagers having farming or/and farming related activities also endured badly as many of them lost their crops and animals during the flood. Based on the above, the research suggests that the government or policy planners consider building shelters in strategic locations of the villages immediately to protect the life of the people during the flood upsurge in the future and thus reduce their vulnerabilities. It is advisable that a community resilience and preparedness should be well articulated in advance with the involvement of the local people. There should be proper coordination in providing aid to the people during the flood so that all the victims receive them equally to mitigate their economic crises and sufferings. Keywords: Floods of 2014, Malaysian Context, Assessing the loss, Vulnerabilities, Future Protection